2009
DOI: 10.1002/hrm.20277
|View full text |Cite
|
Sign up to set email alerts
|

Employer‐supported volunteering benefits: Gift exchange among employers, employees, and volunteer organizations

Abstract: Gift exchange theory is utilized to explain the growing trend of employers offering employer-supported volunteering (ESV) benefits. This paper views these benefits through the lens of gift exchange and discusses the creation of exchange relationships between the employer and employee and between the volunteer organization and employee. Hypotheses derived from the perspective of the employee are tested with a nationally representative sample of volunteers (n = 3,658). Findings suggest ESV benefits are positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
167
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(180 citation statements)
references
References 51 publications
(64 reference statements)
5
167
0
4
Order By: Relevance
“…More widely, it has been noted that participating in voluntary work is associated with positive feelings for volunteers (Post, 2005), and Tidwell (2005) showed that volunteers who identify with their voluntary employer's vision and values are more satisfied and committed with their volunteering work. These findings resonate with studies on corporate sponsored volunteering, which demonstrate that volunteer involvement leads to beneficial outcomes for the volunteers, the voluntary organization, and the employer who sponsored the volunteering activities (e.g., Booth et al, 2009;Jones, 2010;Rodell, 2013). For example, Caliguri et al (2013) showed that volunteering assignments which included meaningful projects, social support within the voluntary organization, and opportunities for skill development yielded positive benefits for the employer (i.e.…”
Section: Outcomes Of Volunteer Engagementsupporting
confidence: 63%
See 3 more Smart Citations
“…More widely, it has been noted that participating in voluntary work is associated with positive feelings for volunteers (Post, 2005), and Tidwell (2005) showed that volunteers who identify with their voluntary employer's vision and values are more satisfied and committed with their volunteering work. These findings resonate with studies on corporate sponsored volunteering, which demonstrate that volunteer involvement leads to beneficial outcomes for the volunteers, the voluntary organization, and the employer who sponsored the volunteering activities (e.g., Booth et al, 2009;Jones, 2010;Rodell, 2013). For example, Caliguri et al (2013) showed that volunteering assignments which included meaningful projects, social support within the voluntary organization, and opportunities for skill development yielded positive benefits for the employer (i.e.…”
Section: Outcomes Of Volunteer Engagementsupporting
confidence: 63%
“…Similarly, research on corporate volunteering programs suggests that employees who are supported by their employer dedicate more time to volunteering (e.g., Booth et al, 2009). …”
Section: Antecedents Of Volunteer Engagementmentioning
confidence: 99%
See 2 more Smart Citations
“…After data collection, we performed a statistical single factor test to evaluate whether common method bias was a problem in our dataset. Since there are few techniques to detect common method bias for formative scales (Booth, Park, & Glomb, 2009), we conducted Harman's one-factor test (Scott & Bruce, 1994;Podsakoff & Organ, 1986;Zhou et al, 2008;Patel & Cardon, 2010;Messersmith & Guthrie, 2010), which is commonly used to assess the existence of common method variance at item level.…”
Section: Controlling For Common Methods Biasmentioning
confidence: 99%